Influence of fabric structure and loop length on thermal comfort properties of cotton/polyester knitted fabrics (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
Thermal comfort characteristics of polyester and cotton fibres blends (100:0, 50:50 and 0:100) having in four differentstructures, such as single jersey, cross tuck, cross miss and twill, at two different loop lengths (0.29 cm and 0.32 cm) havebeen studied. The results evidently prove that the knitted fabrics made from 100% polyester show better thermal comfortproperties, possessing an appreciable comfort level; hence they are applicable for active sportswear textiles. The structureand the loop length of the fabric influence the thermal property to a greater extent. The fabric knitted from 100% polyesterwith a cross-miss structure on a loop length of 0.32 cm shows an excellent thermal comfort characteristic as compared toother samples due to its suitable thermal conduction behavior.